2018
DOI: 10.4103/eus.eus_18_17
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic pancreas in the upper gastrointestinal tract: Is endosonographic diagnosis reliable? Data from the German Endoscopic Ultrasound Registry and review of the literature

Abstract: Background:Ectopic pancreas (EP) belongs to the most frequent subepithelial lesions (SELs) of the upper gastrointestinal (GI) tract. In the majority of cases, it is detected incidentally. Differential diagnosis from mesenchymal subepithelial tumors may be difficult.Methods:Among 24,308 endosonographic examinations and interventions, which were prospectively enrolled in the database of the German Endoscopic Ultrasound (EUS) Registry from January 2009 to August 2013, 575 were performed for suspected SELs of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 59 publications
0
27
0
Order By: Relevance
“…Gottschalk U et al mention in their study that the use of EUS, although helpful in the diagnosis of subepithelial lesions, has limited efficacy in differentiating an ectopic pancreas from other lesions with similar appearance such as gastrointestinal stroll tumours (GISTs), submucosal neuroendocrine tumours, hamartomas and schwannomas. They also note a discordance in literature regarding the echographic characteristics of the ectopic pancreas [ 13 ]. A potential advantage of EUS is the ability to perform a fine-needle biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Gottschalk U et al mention in their study that the use of EUS, although helpful in the diagnosis of subepithelial lesions, has limited efficacy in differentiating an ectopic pancreas from other lesions with similar appearance such as gastrointestinal stroll tumours (GISTs), submucosal neuroendocrine tumours, hamartomas and schwannomas. They also note a discordance in literature regarding the echographic characteristics of the ectopic pancreas [ 13 ]. A potential advantage of EUS is the ability to perform a fine-needle biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…In the asymptomatic patient, periodic customized monitoring is an option. Medical treatment is not effective for symptomatic patients, and localized surgical excision has been shown to be reasonable unless malignant transformation has occurred [ 9 ]. Surgical resection is preferred to endoscopic resection when the muscularis propria is involved.…”
Section: Discussionmentioning
confidence: 99%
“…Two decades ago, a cellulose-based ultrasound contrast agent was approved to improve sonographic evaluation of the upper abdomen (stomach, duodenum and pancreas); the agent was safe and well-tolerated (Lev-Toaff et al 1999;Lund et al 1992;Sisler and Tilcock 1995). Recently, it was suggested that transabdominal ultrasound after oral administration of a cellulose-based gastric contrast agent (TUS-OSCA) is effective in initial screening of gastric lesions (Gottschalk et al 2017;Ignee et al 2017;Liu et al 2014Liu et al , 2015Liu et al , 2016Liu et al , 2017Yegin and Duman 2016;Zheng et al 2016). The aim of this study was to explore the accuracy of TUS-OSCA in the evaluation of gastric emptying.…”
Section: Introductionmentioning
confidence: 99%